Chapter Introduction Organizational interventions: Where we are, where we go from here? - Nielsen, Karina (Taylor & Francis, 2018)
This chapter discusses the need for understanding what works for whom in which circumstances from a research and a policy perspective. It reviews state-of-the-art of evidence base on what works for whom in which circumstances, that is which tools and methods may work in which contexts. Organizational interventions often employ a participatory approach, where employees and managers through ongoing negotiations and discussions decide on the process and the content of the intervention. The demands for understanding how to design, implement and evaluate organizational interventions have arisen both from research and from policy. K. Nabe-Nielsen and R. Randall argued that interventions should be tailored to the organizational context and to the individuals within the organizations. The national policies all recommend that senior managers are involved in promoting the project, and in the management standards emphasize the role line managers have in the daily running of organizational interventions. The chapter also presents an overview of the key concepts discussed in this book.